ALQURAN DAN FILSAFAT (Alquran Inspirator Bagi Lahirnya Filsafat) - Ahmad Asmuni (UIN Siber Syekh Nurjati Cirebon, 2017)
The Muslim guideline which is the main guide (hudan) for humans is the Qur'an. In the Qur'an of Allah Swt. many ordered humans to always use their minds (thinking, philosophizing). In the Qur'an there are also many verses that give encouragement to humans to always use and always develop their minds and hearts. The Koran encourages many people to think about the creation of the heavens, earth, humans, nature, plants, animals, and so on. The Qur'an strongly denounces those who behave taqli d and jumu> d to the inheritance of their ancestors so that they are reluctant to use their minds to think the truth and think freely in order to reach the truth. God's command is related to the command to use this mind, in line with a philosophy that uses reason. Thus, it is understandable that the Qur'an actually instructs humans to philosophize. In fact, the Qur’an has inspired the birth of philosophy. Therefore, it is understandable that many are born of Muslim thinkers (Philosophers) who are famous especially in classical times such as; al-Razi, Ibn Rushd, al-Ghaza>li>, and others.